2021
DOI: 10.1101/2021.11.19.21266578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Causal effect of adiposity on the risk of 19 gastrointestinal diseases: a Mendelian randomization study

Abstract: ObjectivesWe applied Mendelian randomization (MR) to investigate the causal associations of body mass index (BMI) and waist circumference (WC) with 19 gastrointestinal (GI) disorders.DesignMR study.SettingThe UK Biobank, Genetic Investigation of Anthropometric Traits (GIANT) Consortium, FinnGen consortium, and genome-wide association studies.ParticipantsOverall, >400,000 UK Biobank participants, >170,000 participants of Finnish descent, and numerous consortia participants with predominantly European ance… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…NAFLD data (1483 cases, 17,781 controls) was not from UKB or FinnGen study. In this study, genetically predicted BMI and WC were robustly associated with an increased risk of NAFLD 30 . BMI is not an index that can accurately measure abdominal obesity.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…NAFLD data (1483 cases, 17,781 controls) was not from UKB or FinnGen study. In this study, genetically predicted BMI and WC were robustly associated with an increased risk of NAFLD 30 . BMI is not an index that can accurately measure abdominal obesity.…”
Section: Discussionmentioning
confidence: 66%
“…In this study, genetically predicted BMI and WC were robustly associated with an increased risk of NAFLD. 30 BMI is not an index that can accurately measure abdominal obesity. As an anthropological index for measuring abdominal obesity, WC cannot distinguish visceral fat from subcutaneous fat.…”
Section: Discussionmentioning
confidence: 99%
“…This substantial decrease in adipose tissue could explain our results, given that obesity has been identified as a causal risk factor for most of the outcomes presented in our study. Mendelian randomization studies have confirmed that increased adiposity is causally associated with an increased risk of CVDs, 38 GI diseases, 39,40 depression, 41 cancers, 42,43 and reproductive conditions 44 …”
Section: Discussionmentioning
confidence: 99%